2020
DOI: 10.1088/2516-1075/abb379
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution angle-resolved photoemission spectroscopy and microscopy

Abstract: This review outlines fundamental principles, instrumentation, and capabilities of angle-resolved photoemission spectroscopy (ARPES) and microscopy. We will present how high-resolution ARPES enables to investigate fine structures of electronic band dispersions, Fermi surfaces, gap structures, and many-body interactions, and how angle-resolved photoemission microscopy (spatially-resolved ARPES) utilizing micro/nano-focused light allows to extract spatially localized electronic information at small dimensions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 154 publications
1
21
0
1
Order By: Relevance
“…We have thus far considered material parameters relevant for the theoretical calculations in Ref. [6], and shown that the assumption of low renormalization of the fermionic state makes sense, at least at a low temperature of T = 10 −7 eV, corresponding to T ≈ 10 −3 K. ARPES experiments are however typically performed at significantly higher temperatures [41][42][43][44][45][46][47]. We choose T = 2.2 meV, corresponding to T ≈ 25 K, as a temperature which is readily achievable experimentally.…”
Section: Towards Experimental Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…We have thus far considered material parameters relevant for the theoretical calculations in Ref. [6], and shown that the assumption of low renormalization of the fermionic state makes sense, at least at a low temperature of T = 10 −7 eV, corresponding to T ≈ 10 −3 K. ARPES experiments are however typically performed at significantly higher temperatures [41][42][43][44][45][46][47]. We choose T = 2.2 meV, corresponding to T ≈ 25 K, as a temperature which is readily achievable experimentally.…”
Section: Towards Experimental Measurementmentioning
confidence: 99%
“…Each set of figures is then convolved with two different sets of assumed energy, E, and momentum, k, resolutions. The upper panels include state-of-the-art, synchrotron ARPES resolutions (∆E = 1 meV, ∆k = 0.005 Å−1 ) [43][44][45]. The lower panels include good lab-based resolutions, (i.e.…”
Section: Towards Experimental Measurementmentioning
confidence: 99%
“…Over the past decades, there have been great improvements in synchrotron-based light sources which, together with new and more versatile electron analyzers, have pushed the energy and momentum-space resolutions in ARPES experiments to unprecedented levels. 4,5 In parallel to this development, ARPES has taken a leap into the time-domain due to the advent of femtosecond high-power lasers that have enabled ultrafast extreme-ultraviolet (XUV) light sources based on high-harmonic generation (HHG) in noble gases 6–10 or non-linear crystals. 11–14 While several successful implementations of time- and angle-resolved photoemission spectroscopy (tr-ARPES) systems have been demonstrated, the technique continues to rapidly evolve and there is still much progress to be made in terms of increased repetition rate, photon flux, improved time and energy resolutions, and photon energy and momentum range coverage, as well as pump versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, there have been great improvements in synchrotron-based light sources which, together with new and more versatile electron analyzers, have pushed the energy and momentum-space resolutions in ARPES experiments to ever increasing levels 4,5 . In parallel to this development, ARPES has taken a leap into the time-domain due to the advent of femtosecond high-power lasers that have enabled ultrafast extreme-ultraviolet (XUV) light sources based on high-harmonic generation (HHG) in noble gases [6][7][8][9] or nonlinear crystals [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%